Stakeholders Management in the Collection and Commercialization of Brown Macroalgae in the District of Marcona, Nazca, Peru - Contreras, Julie; Solis, Pilar Canales; Tostes, Marta (European Journal of Sustainable Development, 2018)
The Peruvian biodiversity management requires that stakeholders are linked to take advantage of commercial opportunities fulfilling with regulations that facilitate their sustainability. Worldwide, the brown macroalgae commercialization is evolving satisfactorily, which is reflected in the increase of its exports. In Peru, the brown macroalgae activity has a social and cultural importance, as it is done by artisanal fishermen and their families, who depend totally or partially on these resources. However, the increase in demand has had a strong impact on the marine biomass which generated continuous concern of local authorities, sector entities and other stakeholders. Therefore, we are looking to integrate initiatives among stakeholders to generate governance. This article analyzes the linkages networks between the previously mentioned actors and concludes that the average link density level is 37.89%. The main actors that can mediate to strengthen these links are the Peruvian Sea Institute and the Ministry of Production, in a joint effort with the local governments and the environmental police. The latter would allow the use of this important resource with a sustainable development framework. Keywords: Brown Macroalgae, Biocommerce, Artisan Fishermen, sustainable governance, sustainable development